An Insightful Review on Educational Big Data Analytics in Cloud-based e-Learning System - Anita Kanavalli, Ganeshayya Shidaganti, Prakash S, Srinivasa K G (International Journal of Advanced Science and Technology, 2019)
With the rapid momentum of progress in the methodology of knowledge delivery system in existing cloud-based e-learning system, there is also a rising awareness of the complexity of the upcoming educational big data in present times. In current era of cloud computing, there has been various research-based implementations toward leveraging analytical operation along with presence of wide ranges of analytical tools. However, there is no much reported tool to offer educational-based big data analytics. This problem has been addressed by various researchers with an aid of conceptualized, analytical, qualitative, and quantitative models. Therefore, the contribution of the proposed manuscript is to perform an exhaustive review of big data-based approaches as well as research-based analytical tools presented by various researchers in the form of advantages and limitation as well as exploration of open research issues.Keywords: Analytics, Big Data, Education, Learning Management system, e-leaning, Data Mining, Knowledge discovery.